Traces of the Armed Conflict in Casanare due to Oil Exploitation in the 1990s (2016)
Since the nineties, Casanare has undergone an economic and social transformation due to the incursion of the oil industry, this phenomenon strengthened paramilitary structures that carried out serious violations ofhuman rights as a consequence of a neoliberal political of private security to Favoring the economic interests of multinational corporations, resulting in thousands of victims of displacement, forced disappearance and other crimes against humanity.